베트남 관련 전근대 디지털 역사자료의 소개와 활용 - 주성지; Joo Sung-jee (인문학연구, 2017)
디지털 역사자료는 역사 연구의 기본이 되는 사료를 디지털로 전환하여 인터넷을 통해 제공되는 것을 말한다. 디지털로 구성되었다는 점과 네트워크를 통해 인터넷이 연결된 어느 곳에서도 접근할 수 있다는 장점은 역사연구에 큰 영향을 끼쳤다. 베트남사에 대한 역사연구는 어느 정도 진척되었고, 특히 2000년대 후반에 들어 활발하게 진행되었다. 하지만, 전근대 베트남에 대한 연구는 사료에 대한 접근이 쉽지 않은 상황이다. 이에 국내에서 제공되는 디지털 역사자료 중 베트남사 관련 현황을 정리하여 소개하였다. 베트남사 관련 디지털 역사자료에서는 『고려사』·『조선왕조실록』 등 조선시대 편년자료부터 개인의 문집에 이르기까지 다양하지만, 검색을 통해서 중요한 사료를 찾을 수 있다. 뿐만 아니라 국내에서 제공되는 중국측 사료(명·청실록, 중국정사 외국전)도 소개하였다. 그리고 국외에서 제공되는 디지털 역사자료 중 베트남의 전근대 역사자료를 소개하고 활용하는 방법을 설명하였다. 베트남국립도서관에 소장된 고전적 중 디지털 이미지로 전환되어 인터넷을 통해 제공되는 웹사이트를 소개하고, 그 세부 자료를 분석하였다. 특히 미국 베트남놈보존재단(Vietnamese Nom Preservation Foundation)에서 제공되는 사료 중 史部로 분류된 자료를 분석하여 목록으로 제시하였다. 마지막으로는 한국 역사정보화의 경험을 살려 베트남에서 역사자료를 어떻게 구축한다면 활용도를 높일 수 있는지를 제언하였다. 이와 같은 베트남 관련 디지털 역사자료의 소개를 통해 자료에 대한 접근성을 확보하고, 연구의 활성화를 모색하고자 한다. Digitized historical materials refer to historical materials that are the basis of historical research being digitized and offered on the Internet. They have two major advantages of being digitized and being accessible at any places where there is an Internet connection via the network, having huge impacts on historical research. Historical research on the history of Vietnam has made progress to a certain degree, being active especially in the latter part of the 2000s. It is, however, difficult to do research on the premodern history of Vietnam since there is no easy access to its historical materials. This study set out to arrange and introduce the current state of Vietnamese history based on the digitized historical materials available in South Korea to facilitate the activation of research on the topic by introducing digitized historical materials about the history of Vietnam. There are various digitized historical materials on the history of Vietnam in South Korea from the chronological materials of Joseon including Goryeosa and Annals of the Joseon Dynasty to personal collections of works, and one can find important historical materials through search efforts. Furthermore, the present study introduced China`s historical materials(the annals of Ming and Qing Dynasties and books on foreign states in the official history of China) available in South Korea. It also introduced overseas digitized historical materials on the history of Vietnam and offered explanations about how to make use of them. Also introduced in the present study was a web site that converted classical images housed at the National Library of Vietnam into digital ones and made them available on the Internet. The present study also analyzed its detailed materials. It, in particular, analyzed and catalogued the historical materials classified as Sabu(史部) provided by the Vietnamese Nom Preservation Foundation in the U.S.A.. Finally, it made proposals about how to establish and increase the utilization of historical materials in Vietnam based on the experiences with the informatization of history in South Korea.